Super-resolved three-dimensional near-field mapping by defocused imaging and tracking of fluorescent emitters - Son Taehwang; Moon Gwiyeong; Lee Changhun; Xi Peng; Kim Donghyun (Nanophotonics)
Near-field optics is essential in many nanotechnology applications, such as implementing sensitive biosensing and imaging systems with extreme precision. Understanding optical near-fields at the nanoscale has so attracted the considerable research interest, which use a variety of analytical approaches, most notably near-field scanning microscopy. Here, we show defocused point localization mapped accumulation (DePLOMA), which can overcome many weaknesses of conventional analytical methods. DePLOMA is based on imaging fluorescence emitters at an out-of-focal plane. The acquisition, collection, and accumulation of the position and fluorescence intensity of emitters moving above nanostructures can generate three-dimensional near-field maps of light distribution. The idea enables super-resolution liquid-phase measurements, as demonstrated by reconstruction of near-field created by nanoslits with a resolution determined by emitter size. We employed fluorescent emitters with a radius of 50 and 100 nm for confirmation. The axial resolution was found to be enhanced by more than 6 times above that of diffraction-limited confocal laser scanning microscopy when DePLOMA was used.